2018
DOI: 10.3389/fncir.2018.00106
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide and Small Transmitter Coexistence: Fundamental Studies and Relevance to Mental Illness

Abstract: Neuropeptides are auxiliary messenger molecules that always co-exist in nerve cells with one or more small molecule (classic) neurotransmitters. Neuropeptides act both as transmitters and trophic factors, and play a role particularly when the nervous system is challenged, as by injury, pain or stress. Here neuropeptides and coexistence in mammals are reviewed, but with special focus on the 29/30 amino acid galanin and its three receptors GalR1, -R2 and -R3. In particular, galanin’s role as a co-transmitter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
87
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 594 publications
(830 reference statements)
2
87
0
Order By: Relevance
“…In the central nervous system (CNS), it is distributed in the hippocampus, cerebral cortex, hypothalamus, thalamus, brain stem, and cerebellum structures ( 2 ). In the peripheral nervous system, NPY is stored in the postganglionic sympathetic nerve, and co-stored and co-released with norepinephrine (NE) ( 3 ). An increasing number of studies have found widespread existence of NPY in peripheral tissues, such as the retina, smooth muscle, intestine, bone marrow, and thymus ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the central nervous system (CNS), it is distributed in the hippocampus, cerebral cortex, hypothalamus, thalamus, brain stem, and cerebellum structures ( 2 ). In the peripheral nervous system, NPY is stored in the postganglionic sympathetic nerve, and co-stored and co-released with norepinephrine (NE) ( 3 ). An increasing number of studies have found widespread existence of NPY in peripheral tissues, such as the retina, smooth muscle, intestine, bone marrow, and thymus ( 4 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies using slice electrophysiology show that galanin has an inhibitory effect on LC neuron activity [34,51]. Additionally, it has been suggested that galanin can be released somatodentritically from large dense core vesicles in LC-NE neurons and thereby produce an autoinhibitory effect on LC neuron activity, although this hypothesis has yet to be tested directly [48,52].…”
Section: Discussionmentioning
confidence: 99%
“…piriform cortex, entorhinal cortex) [30], it is difficult to ascribe phenotypes to the subset of NE neurons that endogenously express galanin. The role of noradrenergic-derived galanin in normal and impaired brain function therefore remains unclear (for reviews see [2, [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…1; van den Pol 2012). Given that the behavior and function of a hardwired circuit can be altered via neuromodulatory control (Marder 2012), and that neuropeptides are able to exert their effects in a diffuse and slow-acting manner, neuropeptidergic signaling provides an attractive mechanism by which internal state conditions can flexibly and dynamically affect behavior (Hökfelt et al 2018).…”
Section: Neuropeptides As Candidate Mediators Of Internal Statementioning
confidence: 99%